MARKETING MIX EFFECT TOWARDS CONSUMER SATISFACTION AND ITS IMPACT ON LOYALTY: - Ratnawati, Ema; Mubarokah, Mubarokah; Wijayati, Prasmita Dian (Universitas Nusa Cendana, 2024)
The purpose of this study is to analyze the effect of 4P’s marketing mix (product, price, place, promotion) on consumer satisfaction and analyze the effect of satisfaction on consumer loyalty. This research involves quantitative data collection by distributing questionnaires to a purposively selected sample of 100 consumers of Jeruk Pecel Tulen soy sauce in Surabaya City. The analysis method used is the PLS-SEM (Partial Least Square – Structural Equation Modeling). The results showed that the 4P’s marketing mix variables have a positive relationship with consumer satisfaction, but not all of them have a significant effect. The variables of product and price have a positive and significant effect on satisfaction, while the variables of place and promotion do not have a significant effect on the satisfaction of consumers. Furthermore, satisfaction has a positive and significant effect on consumer loyalty of Jeruk Pecel Tulen soy sauce. The limitation of this study is that other variables can measure customer satisfaction and loyalty besides the marketing mix. However, conducting this research can provide insights for future research in helping companies build stronger relationships with consumers, increase consumer loyalty, and ultimately drive business growth. Keywords: Marketing Mix; Consumer Satisfaction; Consumer Loyalty